2002
DOI: 10.3171/jns.2002.96.3.0532
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of trigeminal neuralgia: an ultrastructural analysis of trigeminal root specimens obtained during microvascular decompression surgery

Abstract: Findings were consistent with the ignition hypothesis of TN. This model can be used to explain the major positive and negative symptoms of TN by axonopathy-induced changes in the electrical excitability of afferent axons in the trigeminal root and of neuronal somata in the trigeminal ganglion. The key pathophysiological changes include ectopic impulse discharge, spontaneous and triggered afterdischarge, and crossexcitation among neighboring afferents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
135
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(152 citation statements)
references
References 64 publications
7
135
1
9
Order By: Relevance
“…However, analysis of anatomical and clinical data supports our concept that at the level of the brainstem, when leaving the trigeminal root, specifically at the REZ, the sensory fibers change their direction to target their proper nuclei in the trigeminal brainstem nuclear sensory complex (TBNSC) (Crissman et al, 1996;Pajot et al, 2000;Devor et al, 2002b;Sindou et al, 2002Sindou et al, , 2006Miller et al, 2009). Consequently, many of the Aβ fibers transmitting tactile information from the orofacial region leave the trigeminal root rostrally in their trajectory to the main sensory nucleus, located at the level of the midpons (Samii and Jannetta, 1981;Sessle, 2000) (Fig.…”
mentioning
confidence: 94%
“…However, analysis of anatomical and clinical data supports our concept that at the level of the brainstem, when leaving the trigeminal root, specifically at the REZ, the sensory fibers change their direction to target their proper nuclei in the trigeminal brainstem nuclear sensory complex (TBNSC) (Crissman et al, 1996;Pajot et al, 2000;Devor et al, 2002b;Sindou et al, 2002Sindou et al, , 2006Miller et al, 2009). Consequently, many of the Aβ fibers transmitting tactile information from the orofacial region leave the trigeminal root rostrally in their trajectory to the main sensory nucleus, located at the level of the midpons (Samii and Jannetta, 1981;Sessle, 2000) (Fig.…”
mentioning
confidence: 94%
“…There have been multiple demonstrations of ephaptic interactions that can lead to ectopic impulse activity, not only between closely apposed uninjured axons (56) but also between injured axons (57,58) and between neighboring dysmyelinated axons (59). It has been suggested that demyelination due to compression is present in some cases of trigeminal neuralgia (2,60,61). It is well established that myelinated axons can produce large external electrical fields in regions where myelin is focally absent (62).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Its pathophysiology has been modeled by the "ignition theory" (11,12), which posits that injured trigeminal neurons fire spontaneously and have a lower threshold for evoked afterdischarges leading to paroxysmal pain. Intraoperative microneurographic recordings in trigeminal nerve fibers after stimulation of the known trigger zone in a TN patient demonstrated afterdischarges that were absent when unaffected facial areas were stimulated (13), loss, demyelination and dysmyelination consistent with NVC of the trigeminal nerve (2). However, recent studies have suggested that only severe neurovascular contact, causing displacement or atrophy of the nerve, is associated with pain in classical TN (3,4), and some studies have questioned whether NVC is necessary and sufficient for TN, since pain can occur and recur in the absence of nerve compression (5,6).…”
mentioning
confidence: 99%
“…Morphological changes in the nerve include nerve deviation, distortion, groove formation, and atrophy. 5 Atrophy of the nerve is seen in most cases of TN 20 and is probably attributable to structural abnormalities such as axonal loss and demyelination, 4,10,12,18 but these morphological changes are difficult to describe objectively. Object.…”
mentioning
confidence: 99%